Untangling the mechanism of 3-methyladenine in enhancing the specific productivity: Transcriptome analysis of recombinant Chinese hamster ovary cells treated with 3-methyladenine - Baek, Eric; Lee, Jae Seong; Lee, Gyun Min (Biotechnology and Bioengineering, 2018)
3-Methyladenine (3-MA) is a chemical additive that enhances the specific productivity (q p ) in recombinant Chinese hamster ovary (rCHO) cell lines. Different from its widely known function of inhibiting autophagy, 3-MA has instead shown to increase autophagic flux in various rCHO cell lines. Thus, the mechanism by which 3-MA enhances the q p requires investigation. To evaluate the effect of 3-MA on transcriptome dynamics in rCHO cells, RNA-seq was performed with Fc-fusion protein–producing rCHO cells treated with 3-MA. By analyzing genes that were differentially expressed following the addition of 3-MA during culture, the role of 3-MA in the biological processes of rCHO cells was identified. One pathway markedly influenced by the addition of 3-MA was the unfolded protein response (UPR). Having a close relationship with autophagy, the UPR reestablishes protein-folding homeostasis under endoplasmic reticulum (ER) stress. The addition of 3-MA increased the expression of key regulators of the UPR, such as Atf4, Ddit3, and Creb3l3, further supporting the idea that the enhancement of ER capacity acts as a key in increasing the q p . Consequently, the downstream effectors of UPR, which include autophagy-promoting genes, were upregulated as well. Hence, the role of 3-MA in increasing UPR pathway could have made a salient contribution to the increased autophagic flux in rCHO cells. Taken together, transcriptome analysis improved the understanding of the role of 3-MA in gene expression dynamics in rCHO cells and its mechanism in enhancing the q p .
Keywords: 3-methyladenine; Autophagy; CHO cell; Specific productivity; Transcriptomes; Adenine; Animals; CHO Cells; Cricetulus; Female; Gene Expression Profiling; Gene Expression Regulation; Immunoglobulin Fc Fragments; Recombinant Fusion Proteins; Sequence Analysis, RNA; Unfolded Protein Response; 3-methyladenine; autophagy; CHO cells; RNA-seq; specific productivity; transcriptome